Pemikiran Tasawuf Syekh Abdur Rauf as-Singkili dan Relevansinya Dalam Menghadapi Tantangan Modern - Nauval Satria Pratama; Dwi Nur Anjani; Zhahira Zahrotunnisa; Suci Dwi Aprilia; Abdul Fadhil (Jurnal Ilmu Pendidikan dan Sosial, 2025)
As the times progress, in addition to the various conveniences obtained, the challenges faced by society are also increasingly complex. Based on these considerations, this research aims to examine the Sufism thought of Sheikh Abdur Rauf as-Singkili and its relevance in facing modern challenges, such as materialism, consumerism, individualism, and cyberbullying that are rampant today. This research uses the literature study method, in which researchers collect, examine, and analyze various relevant sources to understand and dig deeper into his tasawwuf thought. Sheikh Abdur Rauf's tasawwuf thought includes his reinterpretation of the concept of wujudiyyah, the reconciliation of tasawwuf and sharia, the importance of dhikr, and the emphasis on morals based on reason. He emphasized that moral actions must always be based on reason, because reason allows humans to evaluate good and bad behavior. It is concluded that Sheikh Abdur Rauf's Sufism offers relevant solutions to modern challenges. His thought or concept of Sufism emphasizes that true happiness lies in inner peace and harmonious relationships with God and others. With this principle, humans can avoid excessive attitudes such as materialism and consumerism. In addition, the role of reason emphasized by him allows individuals to think carefully before acting, so as to prevent the negative impact of materialism, consumerism, individualism and behaviors such as cyberbullying that can harm themselves and others.